Near-Field Spherical Scanning Antenna Measurements: Probe Deconvolution and Sensitivity - Ronald C. Wittmann; Michael H. Francis (International Journal of Antennas and Propagation)
We define and calculate sensitivity for several actual and simulated probes. Probe sensitivity can have a significant impact on the measurement uncertainty associated with probe deconvolution in near-field spherical-scanning, antenna measurements.